Testing the validity of the proposed ICD-11 PTSD and complex PTSD criteria using a sample from Northern Uganda. Issue 1 (1st December 2016) - Murphy, Siobhan; Elklit, Ask; Dokkedahl, Sarah; Shevlin, Mark
Abstract : Background: The International Classification of Diseases (ICD-11) is currently under development with proposed changes recommended for the posttraumatic stress disorder (PTSD) diagnosis and the inclusion of a separate complex PTSD (CPTSD) disorder. Empirical studies support the distinction between PTSD and CPTSD; however, less research has focused on non-western populations. Objective: The aim of this study was to investigate whether distinct PTSD and CPTSD symptom classes emerged and to identify potential risk factors and the severity of impairment associated with resultant classes. Methods: A latent class analysis (LCA) and related analyses were conducted on 314 young adults from Northern Uganda. Fifty-one percent were female and participants were aged between 18 and 25 years. Forty percent of the participants were former child soldiers ( n =124) while the remaining participants were civilians ( n =190). Results: The LCA revealed three classes: a CPTSD class (40.2%), a PTSD class (43.8%), and a low symptom class (16%). Child soldier status was a significant predictor of both CPTSD and PTSD classes (OR=5.96 and 2.82, respectively). Classes differed significantly on measures of anxiety/depression, conduct problems, somatic complaints, and war experiences. Conclusions: To conclude, this study provides preliminary support for the proposed distinction between PTSD and CPTSD in a young adult sample from Northern Uganda. However, future studies are needed using larger samples to test alternative models before firm conclusions can be made. Highlights of the article: Examine the validity of CPTSD in a non-western sample Separate PTSD and CPTSD classes emerged Former child soldiers were more strongly associated with the CPTSD class CPTSD class reported significantly higher levels of anxiety, depression, somatic complaints and conduct problems